2012
DOI: 10.1016/j.ijscr.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant gastric PEComa – Diagnostic and technical dilemmas

Abstract: This case depicts the aggressive nature of malignant gastric PEComa's. The majority of PEComa's are benign in nature and have a better prognosis. We display here the challenges in ascertaining a definitive diagnosis and management of such patients due to limited clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, there were also some cases with poor prognosis being described such as one patient who had surgery only and died of tumor in the third month. [ 36 ] Researchers also reported that integrated therapy of completed resection and chemotherapy was adopted in a case but the patient had local recurrence and liver metastasis in 22 months and subsequently, died of tumor in 27 months. [ 27 ] And we see that, even the most appropriate management strategy is yet to be defined, surgical resection now almost serves as the predominant treatment and chemotherapy or immunotherapy is considered in cases with trait of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were also some cases with poor prognosis being described such as one patient who had surgery only and died of tumor in the third month. [ 36 ] Researchers also reported that integrated therapy of completed resection and chemotherapy was adopted in a case but the patient had local recurrence and liver metastasis in 22 months and subsequently, died of tumor in 27 months. [ 27 ] And we see that, even the most appropriate management strategy is yet to be defined, surgical resection now almost serves as the predominant treatment and chemotherapy or immunotherapy is considered in cases with trait of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The most common location of GI PEComas-NOS was the colon (n = 32), 5 14 , 36 followed by the small intestine (n = 20), 1 , 15 18 , 36 , 37 rectum (n = 7), 19 24 and stomach (n = 4). 25 , 26 , 36 Of the patients, 43 were females and 27 were males, with a ratio of 2:1. The age at diagnosis ranged from 5.5 to 71 years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reported GI PEComas-NOS were considered to be benign or to have uncertain malignant potential, whereas only 22 cases (22/70) exhibited definite malignant behavior, with local recurrence in 4 cases, metastasis in 19 cases, and tumor-related death in 7 cases. 1 , 9 , 10 , 12 , 15 , 17 , 21 , 26 , 29 , 36 The proposed histologic features indicative of malignancy or high risk for aggressive clinical behavior in GI PEComas-NOS by Folpe et al 38 include infiltrative growth pattern, tumor size (>5 cm), high nuclear grade, tumor necrosis, high mitotic activity (>1/50 HPF), and lymphovascular invasion. A recent case series study of 35 GI PEComas has shown that malignant behavior was statistically significantly associated with marked nuclear atypia, diffuse pleomorphism, and mitoses ≥2/10 HPF, but not with tumor necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However it should be noted that such recurrence could be attributed to a few cases being treated with a combination of chemotherapy and rt after surgical resection 9 . The mean survival time for a malignant pecoma of the terminal ileum is estimated to be 28 months 23 .…”
Section: Discussionmentioning
confidence: 99%